2020
DOI: 10.1177/1066480720934269
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Therapy for Therapists: Barriers and Benefits

Abstract: Personal therapy for therapists is described as a means for advancing personal and professional growth. Therapist problems contribute to boundary disturbance, ethical violation, and incompetence. Benefits of therapy include enhanced counselor reflection and therapeutic alliance. Telehealth therapy overcomes barriers and represents an innovation in self-care and career development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Our review found preliminary evidence that different tele-health treatments may be effective, acceptable, and feasible in treating depression and other mental health symptoms in hospitalized COVID-19 patients. Furthermore, demand for mental health services among underserved populations is increased with the emergence of tele-health, inferred to be due to ease of access and reduced cost for patients and providers ( Botaitis & Southern, 2021 ). It is important to note that there may be significant barriers to delivering treatment via tele-health in certain resource-limited settings.…”
Section: Discussionmentioning
confidence: 99%
“…Our review found preliminary evidence that different tele-health treatments may be effective, acceptable, and feasible in treating depression and other mental health symptoms in hospitalized COVID-19 patients. Furthermore, demand for mental health services among underserved populations is increased with the emergence of tele-health, inferred to be due to ease of access and reduced cost for patients and providers ( Botaitis & Southern, 2021 ). It is important to note that there may be significant barriers to delivering treatment via tele-health in certain resource-limited settings.…”
Section: Discussionmentioning
confidence: 99%
“…When there are a limited number of psychotherapists in an area it is possible for a trainee's current supervisor or a colleague of the supervisor to become involved in a trainee's case (Botaitis & Southern, 2020), through taking on a role as consultant. Even though the ethics code prevents providing identifying information during consultations (APA Ethics Code 4.06), small pieces of information given to the supervisor could be identifying and have significant negative impact on the trainee (Botaitis & Southern, 2020).…”
Section: Confidentiality Issuesmentioning
confidence: 99%
“…When there are a limited number of psychotherapists in an area it is possible for a trainee's current supervisor or a colleague of the supervisor to become involved in a trainee's case (Botaitis & Southern, 2020), through taking on a role as consultant. Even though the ethics code prevents providing identifying information during consultations (APA Ethics Code 4.06), small pieces of information given to the supervisor could be identifying and have significant negative impact on the trainee (Botaitis & Southern, 2020). Particularly special consideration should be made to disclosure of sensitive information pertaining to the trainee-client, such as sexual orientation, which under normal supervisor-trainee activities would otherwise not need to be disclosed to the supervisor as per APA Ethics Code 7.04 (APA, 2017).…”
Section: Confidentiality Issuesmentioning
confidence: 99%
See 2 more Smart Citations